Kidney outcomes with finerenone: an analysis from the FIGARO-DKD study. Issue 2 (22nd April 2022) - Ruilope, Luis M; Pitt, Bertram; Anker, Stefan D; Rossing, Peter; Kovesdy, Csaba P; Pecoits-Filho, Roberto; Pergola, Pablo; Joseph, Amer; Lage, Andrea; Mentenich, Nicole; Scheerer, Markus F; Bakris, George L
ABSTRACT: Background: In FIGARO-DKD, finerenone reduced the risk of cardiovascular events in patients with type 2 diabetes (T2D) and stage 1–4 chronic kidney disease (CKD). In FIDELIO-DKD, finerenone improved kidney and cardiovascular outcomes in patients with advanced CKD. This analysis further explores kidney outcomes in FIGARO-DKD. Methods: FIGARO-DKD (NCT02545049) included patients with urine albumin-to-creatinine ratio (UACR) 30–<300 mg/g and estimated glomerular filtration rate (eGFR) 25–90 mL/min/1.73 m 2 or UACR 300–5000 mg/g and eGFR ≥60 mL/min/1.73 m 2 . Outcomes included two composite kidney endpoints, a composite of ≥40% decrease in eGFR from baseline sustained over ≥4 weeks, kidney failure or renal death, and a composite of ≥57% decrease in eGFR from baseline sustained over ≥4 weeks, kidney failure or renal death. Changes in albuminuria and eGFR slope were also analyzed. Kidney and CV outcomes were evaluated by baseline UACR. Results: A lower incidence rate for the eGFR ≥40% kidney composite endpoint was observed with finerenone compared with placebo, but the between-group difference was not significant [hazard ratio (HR) = 0.87; 95% confidence interval (CI): 0.76–1.01; P = .069]. A greater treatment effect was observed on the eGFR ≥57% kidney composite endpoint (HR = 0.77; 95% CI: 0.60–0.99; P = 0.041) with a 36% relative risk reduction for end-stage kidney disease. A larger magnitude of effect on kidney outcomes was observed with finerenone versus placebo for patients with severely increased albuminuria than with moderately increased albuminuria. Improvements in UACR, eGFR slope and cardiovascular risk were evident in both subgroups with finerenone. Conclusions: The present analyses suggest that finerenone protects against kidney disease progression and cardiovascular events in patients with T2D and early- or late-stage CKD. Graphical Abstract: